2006
DOI: 10.1111/j.1365-2052.2006.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tabby cat locus maps to feline chromosome B1

Abstract: SummaryThe Tabby markings of the domestic cat are unique coat patterns for which no causative candidate gene has been inferred from other mammals. In this study, a genome scan was performed on a large pedigree of cats that segregated for Tabby coat markings, specifically for the Abyssinian (T a -) and blotched (t b t b ) phenotypes. There was linkage between the Tabby locus and eight markers on cat chromosome B1. The most significant linkage was between marker FCA700 and Tabby (Z ¼ 7.56, h ¼ 0.03). Two additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
0
23
1
Order By: Relevance
“…Since our results seem to be discrepant with those presented by Lyons et al (2006), who reported the mapping of Tabby to the same location that we have defined as the Ticked locus, we offer the following clarification. Lyons et al (2006) mapped Tabby under the assumption that a single locus was responsible for all coat pattern phenotypes in the domestic cat.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Since our results seem to be discrepant with those presented by Lyons et al (2006), who reported the mapping of Tabby to the same location that we have defined as the Ticked locus, we offer the following clarification. Lyons et al (2006) mapped Tabby under the assumption that a single locus was responsible for all coat pattern phenotypes in the domestic cat.…”
Section: Discussioncontrasting
confidence: 55%
“…The genomic region for Ticked was ultimately defined as a segment of 3.8 Mb, with conserved synteny to Hsa 8: 23-19.7, 43.1-42.9 Mb. This region is equivalent to that reported by Lyons et al (2006) as linked to the Tabby locus. The defined segment occurs within a region showing an intrachromosomal break in synteny between cat and human, and an interchromosomal break between cat and dog (Table 2).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Our 31 microsatellite loci included 2 of the 3 loci (including FCA700 and FCA559, except locus FCA254), as reported by Lyons et al (2006) to be linked with the tabby gene. Schmidt-Kuentzel et al (2009) found significant linkage to the O locus for the markers FCA1466 and FCA1494.…”
Section: Discussionmentioning
confidence: 99%
“…Some breeds of cat are genetically distinct and have several inherited diseases (Lyons et al, 2006), which can be used as models of hereditary and infectious diseases (Dow et al, 1987). There is only 1 outbred stock of orange tabby cats in China, which has been maintained by the North China Pharmaceutical Group New Drug Research and Development Limited Company.…”
Section: Discussionmentioning
confidence: 99%